Trends in citizen education for the upper secondary level in Mexico and a proposal from citizen laboratories - Aguilar Nery, Jesús (2025)
The purpose of this article is to analyze the current trends in citizenship education for students of Higher Secondary Education in Mexico (EMS) and also an alternative proposal to encourage participation through the Citizen Laboratories (citilabs) in the social context. Therefore to develop these approaches we are based on a documentary analysis of recent official and academic sources, from a critical stance and based on the sociological approaches of the citilabs. As part of the findings we found that there are more convergences than divergences between the citilabs and the new MCC, so it is proposed to use the former as a complement to the latter, to carry out activities that contribute to the citizen training of the Mexican EMS.